Gelatin membranes for wound care - Kristinn Páll Sigurbjörnsson 1993- (2019)
Wounds can have significant influence on individuals and it can affect health and quality of life. Three different types of gelatin, porcine skin (PSG), cold water fish skin (FSG) and Atlantic cod skin gelatin (ac-FSG), were used to make gelatin membranes to test their potential for use in wound care. Two plasticizers, mannitol, and sorbitol were used in three different concentrations to improve properties of the membranes. The results indicated that mannitol was not a suitable plasticizer. While sorbitol showed plasticizer effect on the membranes particularly for the highest concentration. The effect of adding two cross-linker, ferulic acid, and tannic acid, in three different concentrations was tested. Ferulic acid didn’t appear to have much cross-linking effect. Tannic acid seemed to have more cross-linking effect. Addition of tannic acid to ac-FSG membrane reduced the solubility of ac-FSG membranes. The ac-FSG and FSG membranes that did not contain tannic acid dissolved after 24 hours in PBS at room temperature. Drug release experiment for two drugs, diclofenac and levofloxacin, was done for gelatin membranes without additives and with 0.1 gram of cross-linkers. ac-FSG membranes showed the fastest diclofenac release for both cross-linkers. While FSG membrane showed the fastest release for membranes without additives. Drug release time was shorter for FSG and ac-FSG membranes than for PSG membranes, except for the ac-FSG membrane with tannic acid where the release time was similar to PSG membranes. Levofloxacin membranes released the drug faster than the diclofenac membranes. The release time for PSG membrane with ferulic acid was the shortest while the release time was longest for PSG membrane with tannic acid. The FSG and PSG membranes without additives had a similar release of levofloxacin. Antimicrobial activity test showed that PSG and FSG membranes with levofloxacin without additives had antibacterial activity against Staphylococcus aureus and Escherichia coli. Sár geta haft mikil áhrif á einstaklinga ...